If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + -7 = -11x + 16 Reorder the terms: -7 + -10x = -11x + 16 Reorder the terms: -7 + -10x = 16 + -11x Solving -7 + -10x = 16 + -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. -7 + -10x + 11x = 16 + -11x + 11x Combine like terms: -10x + 11x = 1x -7 + 1x = 16 + -11x + 11x Combine like terms: -11x + 11x = 0 -7 + 1x = 16 + 0 -7 + 1x = 16 Add '7' to each side of the equation. -7 + 7 + 1x = 16 + 7 Combine like terms: -7 + 7 = 0 0 + 1x = 16 + 7 1x = 16 + 7 Combine like terms: 16 + 7 = 23 1x = 23 Divide each side by '1'. x = 23 Simplifying x = 23
| 3(u+9)=-4(3u-6)+6u | | x-146=70+10x | | 9x^3-15x^2+2=0 | | (cos(x)*cos(y)-cot(x))dx-(sen(x)*sen(y))dy=0 | | (cos(x)*cosy-cot(x))dx-(sen(x)*sen(y))dy=0 | | (5x)(2x+8y)= | | 3x^2+82x+418=0 | | 6x(30+6)=6 | | .11y+.09(y+8000)=2520 | | 11y+.09(y+8000)=2520 | | (5x)(10xy)= | | 0.5x+2=5x-43 | | 12h=9+84 | | b^2+6b-4=-2 | | 27x=9x-2 | | h(x)=4x^2+36 | | (cosx*cosy-cotx)dx-(senx*seny)dy=0 | | x^2-22x+437=0 | | -46+3x=80+12x | | (cosx*cosy-cotx)dx-(sinx*siny)dy=0 | | 11y=165 | | 3x^2+4x+14=0 | | 0.8+4.8=7.2 | | z-9.2=8.5 | | 6r-1+6r=119 | | 0=1.2z-3.6 | | 11z=99 | | -6.5=1.3y-1.3 | | -6=w+19 | | a+96-16=214 | | -34+1.7x=-11.9 | | 3+7m-1=6m+8-2m |